The world can support far more trees. Planting them can reduce carbon pollution a lot: An interview with professor Tom Crowther. (3rd September 2019) - Field, Matt
ABSTRACT: An interview with professor Tom Crowther of ETH Zurich, one of the authors of a Science article suggesting that re-forestation may be the most effective action countries can take to combat climate change. Planting trees on treeless, non-agricultural, non-urban land at the scale the group suggests could bring carbon pollution down to a level not seen in a century.